Should you use progesterone in a postmenopausal patient with a uterus on chronic vaginal estrogen?. Issue 5 (May 2016) - Fitz‐Gerald, Gwen; Lyon, Corey
Abstract : Evidence‐Based Answer : No. Endometrial hyperplasia has been seen with vaginal estrogens of various types, but this condition is rare and the rate is not different from that associated with placebo (SOR: A, systematic review of RCTs and subsequent RCT). Women at high risk for endometrial carcinoma may benefit from some surveillance if vaginal estrogen is used for more than 1 year, as incidence data for hyperplasia are lacking beyond this time frame (SOR: C, evidence based guideline).